2015
DOI: 10.1111/mec.13426
|View full text |Cite
|
Sign up to set email alerts
|

Discordant patterns of genetic and phenotypic differentiation in five grasshopper species codistributed across a microreserve network

Abstract: Conservation plans can be greatly improved when information on the evolutionary and demographic consequences of habitat fragmentation is available for several codistributed species. Here, we study spatial patterns of phenotypic and genetic variation among five grasshopper species that are codistributed across a network of microreserves but show remarkable differences in dispersal-related morphology (body size and wing length), degree of habitat specialization and extent of fragmentation of their respective hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 99 publications
2
19
0
Order By: Relevance
“…Comparative landscape genetics studies on codistributed species have great potential to design cost‐effective conservation plans focusing on measures favouring a wider set of taxa, but are still relatively scarce. So far, comparative studies have focused primarily on vertebrates, including amphibians (Coster, Babbitt, Cooper, & Kovach, ; Richardson, ; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, ), mammals (Dudaniec et al., ; Frantz et al., ; Muscarella, Murray, Ortt, Russell, & Fleming, ), and fishes (Olsen et al., ) and more occasionally on invertebrates (Engler, Balkenhol, Filz, Habel, & Rödder, ; Ortego, García‐Navas, Noguerales, & Cordero, ; Phillipsen et al., ). These multi‐species studies may allow identifying interspecific differences in the way landscape features influence connectivity and gene flow and provide general guidelines for land management programmes aimed at protecting biological communities or ecosystems (Goldberg & Waits, ; Keller, Holderegger, Strien, & Bolliger, ; Nicholson & Possingham, ; Schwenk & Donovan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative landscape genetics studies on codistributed species have great potential to design cost‐effective conservation plans focusing on measures favouring a wider set of taxa, but are still relatively scarce. So far, comparative studies have focused primarily on vertebrates, including amphibians (Coster, Babbitt, Cooper, & Kovach, ; Richardson, ; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, ), mammals (Dudaniec et al., ; Frantz et al., ; Muscarella, Murray, Ortt, Russell, & Fleming, ), and fishes (Olsen et al., ) and more occasionally on invertebrates (Engler, Balkenhol, Filz, Habel, & Rödder, ; Ortego, García‐Navas, Noguerales, & Cordero, ; Phillipsen et al., ). These multi‐species studies may allow identifying interspecific differences in the way landscape features influence connectivity and gene flow and provide general guidelines for land management programmes aimed at protecting biological communities or ecosystems (Goldberg & Waits, ; Keller, Holderegger, Strien, & Bolliger, ; Nicholson & Possingham, ; Schwenk & Donovan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic divergence can arise as a consequence of purely stochastic processes such as bottlenecks or founder effects, which can lead to genetic drift in genomic regions involved in trait expression (Lande, ; Zhan et al ., ). However, numerous studies have found local adaptation as the main evolutionary force responsible for phenotypic differentiation in natural populations (Kekkonen et al ., ; Oneal & Knowles, ; Ortego et al ., ; see reviews in Merilä & Crnokrak, ; Leinonen et al ., ), and considerable research has been devoted to identify the ecological conditions under which this phenomenon arises (Schluter, ; Nosil & Crespi, ; Räsänen & Hendry, ). Theoretical models have shown that local adaptation can occur even in the face of high gene flow when environmental heterogeneity results in spatially and temporally contrasting selection pressures (Merilä & Crnokrak, ; Räsänen & Hendry, ; see also Edelaar et al ., ; Edelaar & Bolnick, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this species is particularly sensitive to habitat destruction because of its specialist nature and strong dependence on its host plant S. vera (Cordero et al 2007b, Ortego et al 2010. Mioscirtus wagneri is endangered within Western Europe (Hochkirch et al 2016 Cordero et al 2007b, Ortego et al 2015. taking into account the presence/absence of sheep and goat droppings and trying to include areas that have been differentially impacted by grazing.…”
Section: Methodsmentioning
confidence: 99%